2018
DOI: 10.1557/jmr.2018.178
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationships for 3D-printed PEEK intervertebral lumbar cages produced using fused filament fabrication

Abstract: Recent advances in additive manufacturing technology now enable fused filament fabrication (FFF) of Polyetheretherketone (PEEK). A standardized lumbar fusion cage design was 3D printed with different speeds of the print head nozzle to investigate whether 3D printed PEEK cages exhibit sufficient material properties for lumbar fusion applications. It was observed that the compressive and shear strength of the 3D printed cages were 63-71% of the machined cages, whereas the torsion strength was 92%. Printing speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…The formation of a large number of big voids and weak bonding are the characteristics of the sample printed at higher speeds. Basgul and colleagues [91] printed a standardised PEEK lumbar fusion cage and found that printing speeds lower than 25 mm/s should be employed. The highest compressive properties were achieved when lower speeds were chosen for 3D printing of PEEK.…”
Section: Printing Speedmentioning
confidence: 99%
“…The formation of a large number of big voids and weak bonding are the characteristics of the sample printed at higher speeds. Basgul and colleagues [91] printed a standardised PEEK lumbar fusion cage and found that printing speeds lower than 25 mm/s should be employed. The highest compressive properties were achieved when lower speeds were chosen for 3D printing of PEEK.…”
Section: Printing Speedmentioning
confidence: 99%
“…These STL files were sliced and translated to G-Code, a numerical control programming language used by 3D printers for coordinates, using commercially available slicing software (Simplify3D, Cincinnati, OH). Briefly, a 0.785 cm 3 reservoir was printed into a PEEK clip using a PEEKMed filament on an Indmatec HPP 155/Gen 2 3D printer (Apium) [ 47 ]. These semi-circular clips contained either one 4 mm diameter opening (1-hole), or two 2 mm openings (2-hole).…”
Section: Methodsmentioning
confidence: 99%
“…These materials are semi-crystalline thermoplastics having excellent mechanical properties. 9,11 It shows excellent strength, dimensional stability and stiffness and sustains high temperature which replaces metal. Without the requirement of lubrication, it has high wear resistance and low coefficient of friction.…”
Section: What Is Polyether Ether Ketone (Peek)mentioning
confidence: 99%
“…This technology is rapidly growing to fabricate patient-specific implants of bone, https://doi.org/10.1016/j.cegh.2019.01.003 Received 4 November 2018; Received in revised form 17 December 2018; Accepted 3 January 2019 prosthetic, heart and its components. 8,9 In medical, the main aim is to maximise the power-to-weight ratio and create development and innovation by using the high-performance material. PEEK is a high-performance polymer which used for manufacturing of medical implants and devices which has a high capability of load bearing.…”
Section: Introductionmentioning
confidence: 99%